2005
DOI: 10.1016/j.ijfoodmicro.2005.02.002
|View full text |Cite
|
Sign up to set email alerts
|

Studying and modelling the combined effect of temperature and water activity on the growth rate of P. expansum

Abstract: The effect of solutes, water activity (a w , 0.890-0.980) and temperature (5-25 8C) on the mycelial growth rate of Penicillium expansum was evaluated. The growth rate dropped as the temperature and a w of the medium decreased. NaCl was the solute causing the greatest growth rate reduction, followed by glucose, glycerol and sorbitol. Statistical analysis of the results showed a significant effect of solute, a w , temperature and combinations of two or three of these factors ( P b 0.0001). Whatever the solutes a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
40
0
4

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(52 citation statements)
references
References 17 publications
8
40
0
4
Order By: Relevance
“…The results in Table 1 revealed significant effect of each single factor and interaction. These results are in agreement with those reported by Lahlali et al (2005) for the radial growth rate of P. expansum on similarly modified Potato Dextrose Agar medium. Teixidõ et al (1998) have observed similar effects on the growth rate of Candida sake in nutrient yeast dextrose broth.…”
Section: Influence Of a W Temperature And Solutesupporting
confidence: 93%
See 3 more Smart Citations
“…The results in Table 1 revealed significant effect of each single factor and interaction. These results are in agreement with those reported by Lahlali et al (2005) for the radial growth rate of P. expansum on similarly modified Potato Dextrose Agar medium. Teixidõ et al (1998) have observed similar effects on the growth rate of Candida sake in nutrient yeast dextrose broth.…”
Section: Influence Of a W Temperature And Solutesupporting
confidence: 93%
“…(6)) and our statistical and graphical analyses confirm the previous findings that the a w has a greater effect than temperature on radial fungal growth under in vitro conditions (Sautour et al, 2002;Samapundo et al, 2005;Lahlali et al, 2005Lahlali et al, , 2006. Haasum and Nielsen (1998) have likewise observed that the radial growth rate of B. cinerea is more affected by a w than temperature, confirming our particular data on the same fungus.…”
Section: Combined Effect Of a W And Temperaturesupporting
confidence: 89%
See 2 more Smart Citations
“…Models based on multi-factor analyses like those described here are valid only for the specific strain/substrate combination studied and within the experimental domain (Delignette-Muller, 1997; Lahlali et al, 2005bLahlali et al, , 2007. Any extrapolation to other strains or growth substrates or beyond the tested ranges of the considered factors would be hazardous.…”
Section: Discussionmentioning
confidence: 99%